Association between intraoperative fluid balance, vasopressors and graft complications in liver transplantation: A cohort study. - Jordan Larivière; Jeanne-Marie Giard; Rui Min Zuo; Luc Massicotte; Michaël Chassé; François Martin Carrier (PLoS ONE)
Introduction Biliary complications following liver transplantation are common. The effect of intraoperative fluid balance and vasopressors on these complications is unknown. Materials and methods We conducted a cohort study between July 2008 and December 2017. Our exposure variables were the total intraoperative fluid balance and the use of vasopressors on ICU admission. Our primary outcome was any biliary complication (anastomotic and non-anastomotic strictures) up to one year after transplantation. Our secondary outcomes were vascular complications, primary graft non-function and survival. Results We included 562 consecutive liver transplantations. 192 (34%) transplants had a biliary complication, 167 (30%) had an anastomotic stricture and 56 had a non-anastomotic stricture (10%). We did not observe any effect of intraoperative fluid balance or vasopressor on biliary complications (HR = 0.97; 95% CI, 0.93 to 1.02). A higher intraoperative fluid balance was associated with an increased risk of primary graft non-function (non-linear) and a lower survival (HR = 1.40, 95% CI, 1.14 to 1.71) in multivariable analyses. Conclusion Intraoperative fluid balance and vasopressors upon ICU admission were not associated with biliary complications after liver transplantation but may be associated with other adverse events. Intraoperative hemodynamic management must be prospectively studied to further assess their impact on liver recipients' outcomes.